PENDEKATAN PEMBELAJARAN MENDALAM DEEP LEARNING PADA PEMBELAJARAN PAI SMA SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MURID - Donny Fadhly Ansyah; Khairuddin Lubis (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
The increasingly rapid development of technology demands students to possess higher-order thinking skills, particularly critical reasoning, as a crucial competency for adapting to modern life. However, PAI learning at the senior high school level in Indonesia still tends to be text-based and memorization-oriented, resulting in low levels of students' critical thinking skills. This study aims to provide a comprehensive descriptive analysis of the implementation of the Deep Learning approach in PAI learning as an effort to develop students' critical thinking skills. This research employs a literature study method by collecting, recording, and analyzing data from books, journals, articles, and credible sources relevant to the Deep Learning approach and critical thinking skills. The findings of this study indicate that the Deep Learning approach is implemented through three stages: comprehension, application, and reflection, supported by three learning experiences: mindful, meaningful, and joyful learning. Various innovative student-centered learning strategies, such as Project Based Learning, Problem Based Learning, Inquiry-Based Learning, and Discovery Learning, have proven effective within the Deep Learning approach in stimulating higher-order thinking skills in PAI learning. The implementation of this approach transforms PAI learning from merely transferring doctrinal texts into a contextual moral reasoning process, in which students are challenged to analyze social phenomena using Quranic and Hadith perspectives. The success of this Deep Learning approach depends significantly on the adaptive and innovative role of the PAI teacher as a facilitator who guides students from passive thinkers to active and critical thinkers